PREFERED TEACHING METHODOLOGY USED BY UNIVERSITY LECTURERS IN TEACHING EFL READING IN RIAU - Yunus, Melor Md; Novitri (International Journal of Educational Best Practices, 2018)
Teachers and lecturers still play significant roles in guiding their learners in EFL classes in achieving academic success during their study and these educators may become exemplary to foster their learners’ reading habit so they discern reading any types of texts needed, This research objective is to investigate the types of EFL teaching methodologies in teaching reading frequently used by all lecturers teaching both at public and private universities in Riau. There were three methodologies were studied: Audio Lingual and Grammar Translation Methods (traditional or lecturers’ centered) and Communicative Language teaching (as learners’ centered). This study implemented a quantitative research design using 5-Likert Scale questionnaire and 97 respondents were involved in the research. The data were analysed by using descriptive statistics (measuring percentage, standard deviation, mean, and overall mean scores) and inferential statistics (independent t-test and one-way MANOVA). The research has revealed that CLT tended to be used more than AL and GTM. This implied that both public and private universities in Riau preferred using the CLT method. From the quantitative research findings, it showed that lecturers aged between 30 and 40 years old felt more confident in their use of this method compared to other age groups.